Self- vs. External-Regulation Behavior ScaleTM in different psychological contexts: A validation study - de la Fuente, Jesús; Pachón-Basallo, Mónica; Martínez-Vicente, José Manuel; Peralta-Sánchez, Francisco Javier; Garzón-Umerenkova, Angélica; Sander, Paul (Frontiers in Psychology, 2022)
The Self- vs External-Regulation Behavior Theory, SR-ER Theory (2021) model has postulated the Self-Regulation /Non or De-Regulation / Dys-Regulation (SR-NR-DR) continuum in the person and in their context. The model also generates a behavioral heuristic that allows us to predict and explain the variability other dependent behavioral variables in a range of scenarios (clinical, educational, health and technology contexts). Consequently, the objective of this study was to validate the different scales prepared on the basis of the theory presented. A total of 469 students voluntarily completed at different times the five questionnaires presented, to give a total of 1385 completed questionnaires. Using an ex post facto design, descriptive, correlational, confirmatory factorial analysis (CFA), reliability and concurrent validity analyses were carried out. The scales were analyzed individually and as a whole. The results showed acceptable structure of scale and consistent levels of reliability. The five levels generated by the SR-NR-DR (personal and contextual) combinatory heuristic that arises from the theoretical model determined significant differences in the levels of the variables analyzed for each psychological context. We discuss the theoretical implications and the implications for the assessment and improvement of the behaviors analyzed in function of the personal and contextual regulation levels evaluated.